2015
DOI: 10.1007/s13258-015-0381-3
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of gene expression and codon usage in human parasitic helminths

Abstract: Codon usage bias refers to the differences in the occurrence frequency of synonymous codons. To understand the patterns of codon usage in mitochondrial genes we used bioinformatic approaches to analyze the protein coding sequences of W. bancrofti and S. haematobium as no work was reported earlier. It was found that the ENC value ranged from 43 to 60 with a mean of 46.91 in W. bancrofti but varied from 49 to 60 with a mean of 45.17 in S. haematobium, respectively. In W. bancrofti a significant positive correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
3
1
0
Order By: Relevance
“…9 Similarly, the studies on the mitochondrial protein-coding genes of Wuchereria bancrofti and Schistosoma haematobium revealed the mean Nc values as 46.91 and 45.17, respectively. 45 These results supported our present findings. Weak CUB might be beneficial for prompt replication of DNA with potential usage of preferred codons, 23 and it might be associated with high genetic variability in codon usage from evolutionary context.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…9 Similarly, the studies on the mitochondrial protein-coding genes of Wuchereria bancrofti and Schistosoma haematobium revealed the mean Nc values as 46.91 and 45.17, respectively. 45 These results supported our present findings. Weak CUB might be beneficial for prompt replication of DNA with potential usage of preferred codons, 23 and it might be associated with high genetic variability in codon usage from evolutionary context.…”
Section: Discussionsupporting
confidence: 93%
“…Further study on mitochondrial DNA of B. mori revealed that the Nc values ranged from 23.14 to 44.00, with an average of 29.47 . Similarly, the studies on the mitochondrial protein‐coding genes of Wuchereria bancrofti and Schistosoma haematobium revealed the mean Nc values as 46.91 and 45.17, respectively . These results supported our present findings.…”
Section: Discussionsupporting
confidence: 89%
“…demonstrated that the presence of preferred codons in cds of mtprotein coding genes was largely influenced by compositional constraints, which are in conformity with the findings of Butt et al (2014). Similar to our results low CUB was observed in mt-protein coding genes of Wuchereria bancrofti and Schistosoma haematobium (Mazumder, Uddin, & Chakraborty, 2017). In the mitochondrial ND2 gene, it was reported that low CUB might be advantageous for DNA replication in vertebrates (Jenkins & Holmes, 2003).…”
Section: Rscu Analysis and Nucleotide Composition Analysis Togethersupporting
confidence: 92%
“…The mitogenomes of higher plants exhibit distinctive expression patterns, including RNA editing and codon preference [ 28 ]. Codon usage bias is the uneven frequency of synonymous codon usage in coding DNA [ 29 ], meaning that synonymous codons are not uniformly utilized in gene transcripts to encode all amino acids, except for methionine (Met) and tryptophan (Trp) [ 30 ]. Codon usage bias is a widespread phenomenon in the natural world and represents molecular evolution [ 31 ].…”
Section: Discussionmentioning
confidence: 99%